Antibacterial and Antibiofilm Activity of Selected Medicinal Plant Leaf Extracts Against Pathogens Implicated in Poultry Diseases - Olawuwo, Olasunkanmi S.; Famuyide, Ibukun M.; McGaw, Lyndy J. (Frontiers in Veterinary Science, 2022)
Antimicrobial resistant poultry pathogens are responsible for treatment failure and economic losses, and can also be a source of resistant zoonotic infections representing a risk to human health. In 2006 the European Union banned the use of antibiotics as growth promoters in farm animals and other regions are likely to follow suit. Alternative products and strategies are sought to help maintain animal gut health to reduce the prevalence of pathogens in the food chain. The minimum inhibitory concentration (MIC) of organic and aqueous leaf extracts of Alchornea laxiflora, Ficus exasperata, Morinda lucida, Jatropha gossypiifolia, Ocimum gratissimum and Acalypha wilkesiana were tested against bacterial poultry pathogens including Staphylococcus aureus, Enterococcus faecalis, Salmonella spp., Escherichia coli, Campylobacter spp. and fungal species (Aspergillus fumigatus, Aspergillus flavus and Candida albicans) using a 2-fold serial microdilution method. Activity of extracts against biofilms of the pathogens was done using a modified crystal violet staining in vitro assay. The safety of extracts was determined against Vero and Caco-2 cells using a tetrazolium-based in vitro assay. Acetone and cold water extracts of M. lucida had the best activity against three bacteria (MIC = 0.05-0.07 mg/ml) and two fungal (MIC = 0.03-0.15 mg/ml) organisms respectively. The E. coli isolate and A. flavus were the most susceptible bacteria and fungi respectively. Caco-2 cells generally displayed higher selectivity index (SI) values compared to Vero cells and average SI values against Vero and Caco-2 cells for both bacteria and fungi ranged from 0.01 to 4.48 and 0.005 to 16.41 respectively. All plant extracts had good anti-biofilm activity (>50 %) against at least one organism. The disruption of established biofilm growth by the plant samples proved to be more difficult to achieve than efficacy against planktonic forms of bacteria. This study shows that some of the plant species are potential candidates as alternative feed additives in poultry production. In the future, a poultry feed trial to evaluate their in vivo efficacy as herbal feed additives will be conducted.